Molecular and morphological characterization reveals high genetic diversity among okra (Abelmoschus esculentus (L.) Moench) genotypes - Periyasamy, Satheeshkumar; Murugan, Sivaraman; Thayumanavan, Sabesan; Sundaramoorthy, Suganthi; Balraj, Ramya (Plant Science Today, 2026)
This study investigated the genetic diversity of 25 okra (Abelmoschus esculentus (L.) Moench) genotypes using phenotypic and molecular characterization methods. Phenotypic analysis of 11 quantitative traits revealed significant divergence among accessions, particularly for traits such as the coefficient of infection, average fruit weight, fruit yield and number of fruits per plant. High Phenotypic Coefficient of Variation (PCV) and Genotypic Coefficient of Variation (GCV) values were observed for plant height, number of branches per plant, number of nodes per plant, average fruit weight, fruit yield and coefficient of infection. High heritability with genetic advance as a percentage of mean was observed for plant height, number of branches per plant, number of nodes per plant, internodal length, number of fruits per plant, fruit length, fruit girth, average fruit weight, fruit yield and coefficient of infection. The germplasm was categorised into six groups after Mahalanobis D2 analysis. Molecular characterisation of the 50 SSR markers identified substantial genetic diversity. 21 markers were polymorphic, exhibiting 2-4 alleles per locus. Fifteen SSR markers showed high polymorphism information content values exceeding 0.5, with a range of 0.41 to 0.8. Jaccard's similarity coefficient ranged from 0.17 to 0.86 (average 0.63). Phenotypic and molecular analyses clustered the genotypes into six distinct groups, underscoring the considerable genetic variability within the studied okra germplasm. These findings provide valuable resources for future okra breeding programs.